El Cabildo y el visitador: la reforma de policía en Lima, 1784-1787 - Montalvo, Enmanuel (2022)
The Bourbon reforms sparked a political struggle between the local elite and the Spanish officials commissioned to execute them. This is a key issue since, in the long term, successful implementation relied on a coincidence of interest between both groups. The police reform is a clear example of how this political struggle was key to defining a specific body of legislation for the city and Cabildo of Lima, governed by guidelines established by the Crown, but also resulting from intense negotiation between the local elite and visitador Jorge de Escobedo.